2012
DOI: 10.1007/s11430-011-4358-z
|View full text |Cite
|
Sign up to set email alerts
|

N and O isotopes and the ore-forming mechanism of nitrate deposits in the Turpan-Hami Basin, Xinjiang, China

Abstract: The recently discovered nitrate ore field in the Turpan-Hami Basin of western China represents an estimated resource of 2.5 billion tons, and is comparable in scale to the Atacama Desert super-scale nitrate deposit in Chile. The research on this area is rarely carried out, and the origin of the deposits remains uncertain. In this study, new methods were used to systematically analyze N and O isotopes in nitrate minerals collected from the Kumutage, Xiaocaohu, Wuzongbulak, Dawadi, Tuyugou, and Shaer ore deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In addition, the Δ 17 O[NO 3 − ] values of Dawadi were from 14.3‰ to 18.4‰ 7 , with a mean value of 16.24‰, indicating obvious oxygen isotope non-mass fractionation, which suggests that the origin of the deposit was related to atmospheric photochemical reactions. At the same time, previous research suggested that the sodium-nitrate deposits in the northern Turpan-Hami area, in contrast, were mainly formed by long-term deposition of atmospheric nitrate aerosols 7 , 11 .
Figure 3 The casting point of oxygen and nitrogen stable isotope signatures of Dawadi, in comparison with those from the Turpan-Hami area, Mojave Desert, and Atacama Desert.
…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the Δ 17 O[NO 3 − ] values of Dawadi were from 14.3‰ to 18.4‰ 7 , with a mean value of 16.24‰, indicating obvious oxygen isotope non-mass fractionation, which suggests that the origin of the deposit was related to atmospheric photochemical reactions. At the same time, previous research suggested that the sodium-nitrate deposits in the northern Turpan-Hami area, in contrast, were mainly formed by long-term deposition of atmospheric nitrate aerosols 7 , 11 .
Figure 3 The casting point of oxygen and nitrogen stable isotope signatures of Dawadi, in comparison with those from the Turpan-Hami area, Mojave Desert, and Atacama Desert.
…”
Section: Resultsmentioning
confidence: 95%
“…However, there is a lack of systematic investigations and studies on the regional scale of the salt springs and water chemistry types in the fracture zone. Moreover, in addition to conventional atmospheric dry and wet deposition, the early formation of sodium nitrate in the uplands around the Dawadi Depression is also a direct material source 11 , and a portion of the NaNO 3 -rich fluid formed by selective dissolution and leaching by seasonal precipitation enters the lake directly, whereas the other portion is submerged into the subsurface. Under the combined effects of surface water and groundwater from multiple sources, the mineralized material was gradually transported to the Dawadi Depression, which is a closed depression in the southern part of Kuruqtag, forming a nitrate salt lake, and evaporating under the influence of the arid climate to form solid-phase minerals such as nitre, nitronatrite, halite, humberstonite, and salt cake, ultimately forming evaporative depositional solid–liquid coexistence in the salt-lake type potassium nitrate deposit.…”
Section: Resultsmentioning
confidence: 99%
“…All of this information indicates that periodic wetting and the precipitation/dissolution cycling of soluble salts play a very important role in controlling the geochemistry of all these waters. The vadose zones of these environments, as well as the shallow groundwaters, can accumulate large amounts of very soluble ions, such as nitrate (Finstad et al, 2016;Lybrand et al, 2013;Qin et al, 2012). High NO 3 − + NO 2 − concentrations in groundwater are observed in other hyper-saline systems such as the Negev Desert, and Central Australia (Barnes et al, 1992;Rosenthal et al, 1987).…”
Section: Implications For Other Hyper-arid Environmentsmentioning
confidence: 99%
“…The obtained results of the formation process and salt-forming age of the Kumish basin were, in fact, relatively consistent. The research on nitrate sources is relatively mature, mainly including the following opinions: (1) NO 3 is related to the capillary transport of groundwater evaporation [9]; (2) volcanic rocks, subvolcanic rocks, and ancient volcanoes in the mining area are the main sources of NO 3 - [10,11]; (3) NO 3 is derived from metal-catalyzed photochemical reactions [12]; (4) NO 3 can be derived from biological nitrification and nitrogen fixation processes in Jurassic coal measure strata [13,14], (5) NO 3 are associated with deep brines [15], and (6) NO 3 is of atmospheric origin [16,17]. The main view of atmospheric sedimentation as the source of nitrate in the nitrate deposit in the Kumish basin has been widely accepted by scholars.…”
Section: Introductionmentioning
confidence: 99%